Analisis Semiotika Roland Barthes Pada Lirik Lagu “Aisyah Istri Rasulullah” Syakir Daulay - Nanda, Rahmat Pike Pirnanda (Communications, 2023)
This research is motivated by the presence of a cover single entitled Religion, a song performed by a singer and actor from Aceh, entitled "Aisyah Istri Rasulullah" has topped and became trending on Youtube. The song he sings contains a certain message, one of the messages is the value of love in the household. In this research, the main theory used is Roland Barthes' semiotic theory. The method used in this research is a qualitative method with a descriptive interpretive approach. This article will review the romance of love in the household contained in the lyrics of the song. This allows the listening audience to receive messages in the form of the values ​​of love and romance in the household, which will then be transmitted from generation to generation to the next generation. In mythology, there are many ways a married couple expresses their affection in their household in their daily life. This expression of feelings is the fruit of a person's love for his partner.